PA28α/β Promote Breast Cancer Cell Invasion and Metastasis via Down-Regulation of CDK15 - Li, Shengnan; Dai, Xiaoqin; Gong, Kunxiang; Song, Kai; Tai, Fang; Shi, Jian (Frontiers in Oncology, 2019)
PA28α/β activated immunoproteasome frequently participates in MHC class I antigen processing, however, whether it is involved in breast tumor progression remains largely unclear. Here, our evidences show that PA28α/β proteins are responsible for breast cancer cell migration and invasion in vitro as well as metastasis in vivo. Knockdown of immunoproteasome core subunit β5i also robustly suppresses the tumor cell migration and invasion. Interestingly, silencing of PA28α/β and β5i up-regulates the protein expression of cyclin-dependent kinase 15 (CDK15). Our data further indicate that the loss of CDK15 is important for breast tumor cell invasion and metastasis. Taken together, this study implicates that targeting of PA28α/β represents a potential way for treatment of metastatic breast cancer.